Identification of Vesicle Transport Proteins via Hypergraph Regularized K-Local Hyperplane Distance Nearest Neighbour Model - Fan, Rui; Suo, Bing; Ding, Yijie (Frontiers in Genetics, 2022)
The prediction of protein function is a common topic in the field of bioinformatics. In recent years, advances in machine learning have inspired a growing number of algorithms for predicting protein function. A large number of parameters and fairly complex neural networks are often used to improve the prediction performance, an approach that is time-consuming and costly. In this study, we leveraged traditional features and machine learning classifiers to boost the performance of vesicle transport protein identification and make the prediction process faster. We adopt the PsePSSM feature and our proposed new classifier HG-HKNN to classify vesicular transport proteins. We address dataset imbalances with random undersampling. The results show that our strategy has an AUC of 0.870 and an MCC of 0.53 on the benchmark dataset, outperforming all state-of-the-art methods on the same dataset, and other metrics of our model are also comparable to existing methods.